Do EMO-operated Charter Schools Serve Disadvantaged Students? The Influence of State Policies - Natalie Lacireno-Paquet (Arizona State University, 2004)
There is a paucity of research about how the policies enacted by states either foster or hinder charter schools' service to disadvantaged students or how the characteristics of charter schools themselves affect this outcome. By combining data from the US Department of Education's Schools and Staffing Survey with data on the characteristics of state charter school policies, this article examines how different types of charter schools respond to the policy and market signals established by state charter legislation, and the impact of such signals on the willingness and ability of charter schools to serve disadvantaged student populations. With a sample of 533 charter schools in 13 states, models are estimated to discern whether specific state policies and whether being managed by two types of for-profit educational management organizations (EMOs)-large and small ones-encourages or discourages schools from enrolling low-income and minority students. The results suggest that certain policy characteristics are important for encouraging schools to serve low-income and minority students. Specifically, having multiple chartering authorities and requiring the transportation of students are important for explaining charter schools' service to low-income and minority students. Being managed by a large-EMO was positively but not significantly related to charter schools enrollment of low-income and minority students. The results differed for small-EMO managed schools. Small-EMOs served significantly lower percentages of minority students. The results suggest that not all charter schools are the same and that policy design and organizational form matters for determining whom charter schools will serve.